Vancomycin-induced gut microbial dysbiosis alters enteric neuron–macrophage interactions during a critical period of postnatal development - Schill, Ellen Merrick; Joyce, Elisabeth L.; Floyd, Alexandria N.; Udayan, Sreeram; Rusconi, Brigida; Gaddipati, Shreya; Barrios, Bibiana E.; John, Vini; Kaye, Mitchell E.; Kulkarni, Devesha H.; Pauta, Jocelyn T.; McDonald, Keely G.; et al. (Frontiers in Immunology, 2023)
Vancomycin is a broad-spectrum antibiotic widely used in cases of suspected sepsis in premature neonates. While appropriate and potentially lifesaving in this setting, early-life antibiotic exposure alters the developing microbiome and is associated with an increased risk of deadly complications, including late-onset sepsis (LOS) and necrotizing enterocolitis (NEC). Recent studies show that neonatal vancomycin treatment disrupts postnatal enteric nervous system (ENS) development in mouse pups, which is in part dependent upon neuroimmune interactions. This suggests that early-life antibiotic exposure could disrupt these interactions in the neonatal gut. Notably, a subset of tissue-resident intestinal macrophages, muscularis macrophages, has been identified as important contributors to the development of postnatal ENS. We hypothesized that vancomycin-induced neonatal dysbiosis impacts postnatal ENS development through its effects on macrophages. Using a mouse model, we found that exposure to vancomycin in the first 10 days of life, but not in adult mice, resulted in an expansion of pro-inflammatory colonic macrophages by increasing the recruitment of bone-marrow-derived macrophages. Single-cell RNA sequencing of neonatal colonic macrophages revealed that early-life vancomycin exposure was associated with an increase in immature and inflammatory macrophages, consistent with an influx of circulating monocytes differentiating into macrophages. Lineage tracing confirmed that vancomycin significantly increased the non-yolk-sac-derived macrophage population. Consistent with these results, early-life vancomycin exposure did not expand the colonic macrophage population nor decrease enteric neuron density in CCR2-deficient mice. Collectively, these findings demonstrate that early-life vancomycin exposure alters macrophage number and phenotypes in distinct ways compared with vancomycin exposure in adult mice and results in altered ENS development.